A General Numerical Approximation of Construction of Axisymmetric Ideal Plastic Plane Deformation of a Granular Material - Nor Alisa, Mohd Damanhuri; Syafikah , Ayob (IOP Publishing, 2017)
A general numerical approximation of the stress equilibrium equations and constructing axisymmetric ideal plastic plane deformation of a granular material is considered. The stress components are assumed to satisfy the Coulomb yield criterion and the self-weight of the material is neglected. The standard method of numerical approximation leads to the construction of the small segments of the stress characteristic field. Using the Matlab program, the method is applied to a problem of granular indentation by a smooth flat surface.